The Role of Environmental and Socioeconomic Factors in Mental Health Well-being: Insight from Jordan - El-Shaer, Ammin Abu; Harbi, Ali Suleiman; Al-Harazneh, Raghad Waleed (West Science Interdisciplinary Studies, 2024)
Background and aims: Depression, anxiety, and stress are among the most common psychological disorders affecting people worldwide. These conditions can influence mental well-being, resulting in sustained feelings of sadness, worry, and hopelessness. This study aims to examine the relationship between environmental factors and psychological disorders (i.e., depression, anxiety, and stress) and to explore the relationship between socioeconomic factors and these psychological disorders, methods: Depression, anxiety, and stress were measured using the Arabic version of Depression, Anxiety, and Stress Scale - 21 items (DASS-21). Spearman's Rank Correlation was used to examine the relationship between environmental and socioeconomic factors and (anxiety, depression, and stress). The results were considered significant at P value ˂ 0.05, and the confidence interval (CI) was 95%. Results: The study included 409 participants. with a mean age of 36.42 years (SD ± 13.259). The majority were female (59.4%), married (57.2%), had a bachelor’s degree (46.5%), and were employed full-time (51.3%). The majority had an income of less than 500 JOD per month (53.5%). A negative significant relationship was found between Depression, anxiety, and stress and all environmental and socioeconomic factors except the proximity of green areas Conclusion: Environmental and socioeconomic factors were found to be significantly associated with mental health, indicating that both environmental and personal financial safety play crucial roles in influencing psychological well-being. These findings suggest that interventions aimed at improving access to natural environments and enhancing home security may be beneficial in promoting mental health and reducing depression, anxiety, and stress levels within the population.